DEVELOPMENT RESOURCES FOR ENERGY IN MODERN UZBEKISTAN (KIUT Publication, 2025)
The integration of clean energy solutions in Uzbekistan—encompassing solar, wind power, biogas derived from organic matter, as well as micro-hydropower harnessed from both natural and manmade water channels—has been a pressing societal issue over the years. Viewing this through a lens that extends into the future, reliance on renewable energy sources is undoubtedly imperative for securing robust energy supplies alongside ensuring environmental and economic stability in the country. Furthermore, it is pivotal not only to foster sustainable development within its energy sector but also to safeguard natural resources for posterity and enhance ecological conditions. Uzbekistan actively promotes the development of renewable energy sources as part of a broader strategy to diversify the energy portfolio, reduce dependence on fossil fuels and address environmental issues. The government aims to generate at least 30% of its electricity from RES by 2030, with a focus on solar and wind energy, given the country's abundant natural resources. Significant investments have been made in solar power projects, such as the Navoi Nur Solar Power Plant, and wind farm developments. Additionally, Uzbekistan is fostering international partnerships and collaborations to enhance its technological capabilities and improve infrastructure related to renewable energy, reflecting a strong commitment to sustainable development and energy security.